Enhanced injection method for synthetically generated turbulence within the flow domain of eddy-resolving simulations. (1st April 2018) - De Nayer, G.; Schmidt, S.; Wood, J.N.; Breuer, M.
Abstract: The quality of eddy-resolving turbulence simulations strongly depends on appropriate inflow conditions. In most cases they have to be time-dependent and satisfy certain conditions for the first (mean velocities) and second-order moments (Reynolds stresses) as well as concerning suitable length scales. To mimic a physically realistic incoming flow, synthetically generated turbulent velocity fluctuations superimposed on the mean velocity field are a valuable solution. However, the resolution of the grid near the inlet has to be sufficiently fine to avoid excessive damping of the turbulence intensity. In order to circumvent this problem, the injection of synthetically generated inflow data not at the inlet itself but inside the flow domain near the area of interest, where the grid is typically much finer, is an elegant loophole. In the present study two different injection techniques based on a source-term formulation are analyzed and evaluated. In addition to these techniques the injected data are weighted by a Gaussian distribution defining the influence area. In the recent work the definition of the influence area is enhanced compared to the initial version of Schmidt and Breuer (2017) extending the application range. The case of a rather small influence area in comparison with the grid cell size is now tackled which is often relevant for industrial applications. The flow past a wall-mounted hemisphere is chosen as test case. The bluff body is exposed to a thick turbulent boundary layer at Re = 50, 000. The generation of the turbulent velocity fluctuations in the present investigation relies on the digital filter concept, but the injection techniques evaluated are not restricted to this inflow generator. The synthetic turbulent velocity fluctuations are injected about one diameter upstream of the hemisphere. Wall-resolved large-eddy simulations are carried out for two grid resolutions and the corresponding results are analyzed and compared with the reference measurements by Wood et al. (2016). Finally, one injection technique is found to be clearly superior to the other, since it guarantees the correct level of the velocity fluctuations and the reproduction of the autocorrelations.